Analysis of the Construction of Infiltration Wells in Pondok Jati Housing, Sidoarjo to Reduce Surface Flow for Flood Prevention Efforts - Fathurokman, Hasan Alif; Wulandari, Esti; Nugroho, Laksono Djoko (Transpublika Publisher, 2025)
Water stored on the surface generally turns into runoff and much faster than groundwater considering the very low flow rate of the latter. Drainage of the Pondok Jati residential area is less able to receive or accommodate rainwater discharge because the development and growth of a city is one of the triggers for increasing the volume of discharge that passes through the residential area. Land use will affect the percentage of water that seeps into the soil with surface flow. Land with dense populations and many buildings, infiltration wells must be made more and larger in volume. Either with individual infiltration wells or with infiltration wells collectively for several houses, the need for infiltration wells from each block to reduce runoff that occurs with a 10-year return period plan. For the specifications of this infiltration well, concrete pipes are used. This infiltration well itself has concrete pipe walls with a diameter of 100 cm (1 meter) with the depth of the infiltration well is 300 cm (3.0 meters) and the number of points needed. The cost of making an infiltration well with a total of 210 infiltration wells in the Pondok Jati Sidoarjo housing complex is Rp. 696.358.600,- .